(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The first experiment involving different explants and concentrations of 2,4-D and kinetin showed highly significant differences for length and weight of callus formed except interaction of callus weight. Leaf explant appeared to be best of all for callus length and weight when 1.0 mg/L 2,4-D + 0.25 mg/L kinetin concentration was used. Similarly, different explants versus different concentrations of BAP/GA3/IAA showed significant differences for shoot length and leaf number per plantlet and also for root length. However, interaction term confirmed node and node/internode explants produced better results in shoot length and number of leaves per plantlet when concentrations 1 .0 mg/L BAP + 0.1 mg/L GA3 and 1.0 mg/L BAP + 0.2 mg/L GA3, 1.0 mg/L BAP + 0.4 mg/L GA3, respectively, were used. Similarly, internode explants produced better results for root length after 21 days plantlet-1 when concentration of 1.0 mg/L IAA + 0.25 mg/L GA3 was used. Shoot tip explants also produced better results in root length after 28 days plantlet-1 when concentrations 1.0 mg/L IAA + 0.25 mg/L GA3 were used. Key Words: In vitro, callus initiation, regeneration, potato. DOI: 10.3329/bjar.v34i3.3971 Bangladesh J. Agril. Res. 34(3) : 449-456, September 2009